Teleocichla wajapi, a new species of cichlid from the rio Jari, Brazil, with comments on T. centrarchus Kullander, 1988 (Teleostei: Cichlidae) - Varella, Henrique R.; Moreira, Cristiano R. (Zootaxa, 2013)
Teleocichla wajapi, new species, is described from the rio Jari basin, northern Brazil. The new species differs from its congeners by possessing four anal-fin spines, 56–62 scales in E1 series, smaller orbital diameter (24.6–30.2% of head length) and barred or zigzag color pattern on flanks. New information on the morphology and distribution of T. cen-trarchus is provided based on recently collected material.